A novação moderna e o novo direito privado - Jadon, Carlos Eduardo (2010)
The current essay addresses the important institute of the law of obligations, novation, with the unpublished covering that grant it the new values that rule Private Law in the constitutional and infraconstitutional scope. By means of a descriptive analysis of the events that modified Law, we verify the evolution of Liberalism to the Welfare State, whose basic principles consist of the preservation of human dignity and the solidarity in the law relations. The appearance of the Post Modern State as a result of the growing power of the big corporations and the longing for the maximization of profits that challenges the values that shape the Social State is also addressed. The analysis of the institute of novation is carried out under these new paradigms, under the support of the new private Law, from its conceptualization to its requirements, types and effects. Bearing in mind that novation is not a contract, but one of its effects, we verify that the values of the Welfare State cannot decline the mere economic, selfish and individual interests of the creditor in the obligational relation nor can the debtor prevail over the acts that result from bad faith. One of the objectives of the new Private Law and Public Law is also ethics in the Law relations. This value becomes clear in the law of obligations when we verify that the parties in the obligational relation have the legal duty to act in good faith. Therefore, this is the interpretation that will prevail in the analysis of the provisions of law that deal with novation and also in any other contract that produces novative effect